Anthraquinone-intercalated V2O5 with Al3+ for superior zinc-ion batteries: reversible transformation between disorder and order. Issue 88 (20th October 2022) - Li, Kai; Lv, Jia; Cao, Tong; Gong, Yun; Zhang, Da Liang
Abstract : Oxygen-deficient anthraquinone (AQ)-intercalated vanadium oxide displays an ultralong lifespan in the electrolyte with Al 3+ due to the dual-pillar of AQ/Al 3+ and reversible disorder–order conversion on the (00 l ) facets. Abstract : Oxygen-deficient anthraquinone (AQ)-intercalated vanadium oxide (1, 8-AQ)0.08 V2 O5 ·0.25H2 O (AQ-VO) was synthesized hydrothermally, which displayed an improved rate capability with an ultralong lifespan in the electrolyte with Al 3+ compared with that in the absence of Al 3+ . These features are associated with the dual-pillar of Al 3+ /AQ in AQ-VO and the dynamic reversible conversion between disorder and order on the (00 l ) facets. Moreover, density functional theory (DFT) calculations discover a small Zn 2+ diffusion barrier of 0.47 eV in AQ-VO.